Application of Aroma Precursors in Food Plant Raw Materials: Biotechnological Aspect - Dubova, Halyna; Bezusov, Anatoliy; Biloshytska, Oksana; Poyedinok, Natalia (Innovative Biosystems and Bioengineering, 2022)
An Author Correction to this article was published on 26 October 2023. The article is devoted to the analysis of the main factors accompanying the use of aroma precursors, in particular, of a lipid nature, in food raw materials. The prerequisites for the impact on the precursors of aroma with the help of plant enzymes are given. The purpose of the article is to analyze the biotechnological aspect, which is based on enzymatic reactions with aroma precursors and enzymes of plant origin. Features of the mechanism of action of lipid precursors are highlighted, their diversity causing various characteristic reactions is analyzed, and possible end products of reactions with certain odors are noted. The attention is paid to the issue of the status of the naturalness of flavor precursors in food products, which varies in different countries. A scheme of factors influencing the formation of aroma from lipid precursors has been developed. The influence of pigments of carotenoid nature on the aroma is considered, namely: examples of instantaneous change of watermelon aroma to pumpkin one due to isomerization of carotenoids are given. The main factors of enzymatic formation of aroma from precursors of polyunsaturated fatty acids for their effective use by creating micromicelles are summarized. A way to overcome the barrier of interaction between lipid precursors of a hydrophobic nature and hydrophilic enzymes has been substantiated. It is proposed to accelerate enzymatic reactions under in vitro conditions and use the vacuum effect to overcome the barrier between enzymes and precursors. To explain the effect of vacuum in a system with enzymes, ideas about disjoining pressure and the reasonable expediency of its use are considered. A schematic process flow diagram for the restoration of aroma lost during the technological processing of raw materials is given; it demonstrates the factors for ensuring interfacial activation conditions for enzymes and aroma precursors.